Implementation of Ethno-STEM Learning through the "Lompek Kodok" Game to Enhance Critical Thinking Ability: Penerapan Pembelajaran Etno-STEM melalui Permainan Lompek Kodok untuk Meningkatkan Kemampuan Berpikir Kritis - Putri, Meisy Haziza; Desy Hanisa Putri , Desy Hanisa Putri; Iwan Setiawan , Iwan Setiawan; Aprina Defianti, Aprina Defianti (SEJ (Science Education Journal), 2024)
The research on the implementation of Etno-STEM learning involves four indicators of Science, Technology, Engineering, and Mathematics based on the culture local wisdom of the surrounding community. This study is crucial for investigating the enhancement of students' critical thinking abilities, as this approach has the potential to broaden insights into the effectiveness of classroom learning and student responses to it. Thus, it can provide a reference for developing learning approaches on how incorporating local values into STEM education can improve academic outcomes and student engagement. This research aims to describe the improvement of students' critical thinking abilities taught with Ethno STEM through the traditional game of Lompek Kodok. It also aims to describe students' responses to the implementation of Ethno-STEM learning. The research was conducted at SMA Negeri 04 Kota Bengkulu with a total of 225 10th-grade students during the first semester of the academic year 2023/2024. The research type used in this study is Pre-Experimental, and the design used is One Group Pretest-Posttest Design. The instruments used were a critical thinking ability test and a response questionnaire for 33 students selected using purposive sampling techniques. The instruments used are critical thinking ability tests and response questionnaires. Data analysis techniques that will measure the improvement of critical thinking abilities include Descriptive Analysis and Inferential Analysis with N-Gain. Meanwhile, descriptive statistical analysis will be used to measure student responses. The research results show that the N-Gain value in class X MIPA 3 is 0,75, indicating that the class is in the high category. Additionally, students' responses to this research are categorized as very good, with percentages as follows: 80% for the attitude towards the process aspect, 87% for interest level, and 82% for clarity towards the process aspect. Overall, Ethno STEM learning can improve students' critical thinking abilities.